PENGARUH DIMENSI KUALITAS LAYANAN KREDIT TERHADAP KEPUASAN DEBITUR USAHA MIKRO DAN KECIL (UMK) PADA BANK TABUNGAN PENSIUNAN NASIONAL - NURUL MUBAROK NURUL (I-Finance Journal, 2016)
The purpose of this study was to determine the influence of the dimensions of service quality credit-BTPN MUR Palembang Area 1 to satisfaction of its debtors. The population of this research is all debtors of BTPN MUR Palembang Area 1 up to December 2011 were 1,500 people consisting of micro and small business borrowers. The amount of sample to be taken is as much as 93 respondents, rounded to 100 respondents. Samples will be taken proportionately from six branches in Palembang Area 1. The data analysis technique used to determine the effect of service quality to satisfaction of the debtor's credit to micro and small enterprises (MSEs) in the People's Bank BTPN Business Partners Palembang Area 1 is to use statistical analysis multiple regression using the F and t test hypotheses. The analysis showed that it is known that the calculated F value of 1284.787 with a significance value of 0.000 is less than 0.05, which means that H0 rejected and Ha accepted. It is clear that the influence jointly on the dimensions of service quality credits include tangible (X1), reliability (X2), assurance (X3), responsiveness (X4), empathy (X5) to the satisfaction of the debtor UMK in BTPN-MUR Palembang Area 1. In the regression equation showed that the most influential dimensions of consumer satisfaction is the dimension of reliability (reliability). Where the influence of the dimensions of reliability is equal to 0.240 so that if the dimensions of reliability is increased by 1 score then the level of customer satisfaction will be increased by 0.240 assuming other variables held constant.Key Word: Service Quality, Satisfaction Debtor and Small and Medium Enterprises